Sleep disturbance in patients with chronic concussive effects - Andrea Hinds; Carla R Jungquist; John J Leddy; Fnu Seemant; John G Baker; Barry Willer (Concussion)
Aim: Sleep disturbance is relatively overlooked in concussion treatment although sleep disorders may prolong or exacerbate symptoms after a concussion. We looked at the incidence of both sleep disturbance and postconcussion symptoms in a sample of recently concussed individuals. Methods & results: We evaluated scores on the insomnia severity index (ISI) and postconcussion symptom scale (PCSS) in 96 participants with persistent symptoms. Sleep disturbance significantly contributed to the severity of postconcussive symptoms and length of recovery; this effect was less pronounced in athletes. Conclusion: These results suggest a relationship between sleep problems and the time course of recovery from concussive injury. Clinicians who regularly treat concussion would benefit from a more thorough consideration of sleep function in the assessment of postconcussive symptoms.